Different Threats, Different Militaries: Explaining Organizational Practices in Authoritarian Armies. (2nd January 2016) - Talmadge, Caitlin
Abstract : Why do some states generate competent, professional military organizations, while others fail to do so even when they have the required economic, demographic, and technological endowments? Variation in states' military organizational practices—their core policies related to promotion patterns, training regimens, command arrangements, and information management—holds the key. This article develops a typology of such practices and explains why and how they vary in response to the internal and external threats facing particular regimes. The article then subjects this argument to a carefully designed plausibility probe comparing the threat environments and military organizational practices of two states whose differences are both intuitively and theoretically puzzling: North and South Vietnam during the period 1954–1975. The initial evidence provides support for the theory and casts doubt on existing explanations of military organizational behavior focused on external threats, democracy, or the degree of political intervention in the military. The findings have important implications for foreign policy, as well as for future research on authoritarianism, civil-military relations, and military effectiveness.